Fabrication and Performance of Laterite East Kotawaringin-Zeolite/Chitosan Composite as Slow Release of Iron Fertilizer - Rendy Muhamad Iqbal; Sri Wardhani; Darjito Darjito; Karelius Karelius (Universitas Jenderal Soedirman, 2018)
Laterite soil is one of natural resources in East Kotawaringin regency, Central Kalimantan, Indonesia, which contains high element of Fe. Fe is one of micronutrients that is needed for plant in slight amount. This study aims to determine the effect of chitosan composition and composition of zeolite : laterite on the release of Fe activities from synthesized fertilizers result. Laterite is characterized by using XRF and XRD. Slow release iron fertilizer is synthesized by eliciting laterite to zeolite matrix. Then, It is stirred into chitosan gel with concentration of 2, 2.6, and 2.8 % for 30 minutes. After Zeolite - laterite - chitosan has been homogenized, then it is dropped into 0.4 M NaOH to form beads. Then testing the release of Fe with the batch method in distilled water. The result showed that the laterite soil is amorphous form, and Fe content reached 80.25 % . The higher the concentration of chitosan which is used , then more Fe is released from fertilizer. Whereas if the amount of zeolite is greater, the slower the release of Fe will be.